The Transcription Factor T-Bet Is Required for Optimal Type I Follicular Helper T Cell Maintenance During Acute Viral Infection - Wang, Pengcheng; Wang, Youping; Xie, Luoyingzi; Xiao, Minglu; Wu, Jialin; Xu, Lifan; Bai, Qiang; Hao, Yaxing; Huang, Qizhao; Chen, Xiangyu; He, Ran; Li, Baohua; et al. (Frontiers in Immunology, 2019)
Follicular helper T cells (TFH cells), known as the primary “helpers” of the germinal center (GC) reaction, promote the humoral immune response to defend against various pathogens. Under conditions of infection by different types of pathogens, many shared transcription factors (TFs), such as Bcl-6, TCF-1 and Maf, are selectively enriched in pathogen-specific TFH cells, orchestrating TFH cell differentiation and function. In addition, TFH cells also coexpress environmentally associated TFs as their conventional T cell counterparts (such as T-bet, GATA-3 or ROR-γt, which are expressed in Th1, Th2 or Th17 cells, respectively). These features likely indicate both the lineage specificity and environmental adaption of the TFH cell responses. However, the extent to which the TFH cell response relies on these environmentally specific TFs is not completely understood. Here, we found that in mouse model of acute Lymphocytic choriomeningitis virus (LCMV) infection, T-bet was specifically expressed in virus-specific TFH cells and that the T-bet-IFN-γ axis was dispensable for the early fate commitment of TFH cells, while essential for the maintenance of differentiated TFH cells, promoting their proliferation and inhibiting their apoptosis during acute viral infection. Microarray analysis showed both similarities and differences in transcriptome dependency on T-bet in TFH and TH1 cells, suggesting the distinctive role of T-bet in TFH cells. Collectively, our findings reveal an important and specific supporting role for T-bet in type I TFH cell response, which can help us gain a deeper understanding of TFH cell subsets.